Ecofriendly Upcycling of Poly(vinyl chloride) Waste Plastics into Precious Metal Adsorbents - Seung Su Shin; Seungho Lee; Sung‐Joon Park; Hansoo Kim; Juyeon Choi; Wangyun Won; Jung‐Hyun Lee (Advanced Science, 2025)
Abstract Global interest in the recycling of precious metals (PMs) in various industrial sectors has spurred the exploration of high‐performance PM adsorbents. Unfortunately, many adsorbents exhibit unsatisfactory PM adsorption performance and require complex fabrication protocols and toxic chemicals. Hence, further development of simple, efficient, and eco‐friendly adsorbents is necessary. Herein, poly(vinyl chloride) (PVC) waste plastics are simply transformed into high‐performance PM adsorbents via benign solvent treatment and hydrazination. The resultant hydrazine‐functionalized PVC (h‐PVC) plastic can effectively recover gold, palladium, and platinum from real‐world leachates owing to its combined reduction and chemisorption mechanisms. The PM‐adsorbed h‐PVC plastic can be regenerated, calcined into high‐purity PMs, or directly employed as a catalyst, demonstrating its practical feasibility. Techno‐economic and life‐cycle assessments reveal that the h‐PVC plastic‐utilizing industrial‐scale recovery of gold from electronic waste is cost‐competitive and environmentally advantageous. The strategy supports environmental and sustainable technologies by enabling the sustainable maintenance of carbon and PM resources and provides an efficient and sustainable method for fabricating advanced adsorbent materials.